Anxiety sensitivity and smoking among Spanish-speaking Latinx smokers. (March 2019) - Zvolensky, Michael J.; Bakhshaie, Jafar; Shepherd, Justin M.; Peraza, Natalia; Garey, Lorra; Viana, Andres G.; Glover, Nina; Brown, Jason T.; Brown, Richard A.
Abstract: Despite the documented health disparities for smoking among the Latinx population, there is limited understanding of transdiagnostic constructs that may help explain smoking among Spanish-speaking Latinx smokers. The present study examined one promising transdiagnostic factor, anxiety sensitivity (fear of anxiety and related sensations), in relation to cigarette dependence, perceived barriers for quitting, and severity of problems experienced when trying to quit among a large sample of Latinx smokers. Participants were 367 Spanish-speaking Latinx daily smokers (59.1% female, M age = 33.20 years, SD = 11.81). As hypothesized, anxiety sensitivity was significantly related to the severity of cigarette dependence, perceived barriers for quitting, and problems when trying to quit. Inspection of the lower-order dimensions of anxiety sensitivity indicated that Physical Concerns was significantly related to cigarette dependence whereas Cognitive Concerns was associated with greater perceived barriers for quitting and severity of problems experienced during past quit attempts. The present study provides novel empirical evidence that anxiety sensitivity is related to a moderate, yet clinically meaningful, proportion of the variance in cigarette dependence, perceived barriers for quitting, and problems experienced during quit attempts. These findings underscore the value of examining anxiety sensitivity among Latinx smokers and focusing greater attention on this construct in efforts to reduce or quit smoking among this population. Highlights: Anxiety sensitivity was related to cigarette dependence, perceived barriers for quitting, and problems when trying to quit. Physical Concerns was related to greater cigarette dependence. Cognitive Concerns was related to greater perceived barriers for quitting and more problems when trying to quit. Targeting anxiety sensitivity in smoking interventions may improve efforts to reduce or quit smoking in Latinx populations.